Scaling up sustainable land management and restoration of degraded land - Thomas, Richard J.; Reed, M.; Clifton, K.; Appadurai, Arivudai Nambi; Mills, A. J.; Zucca, Claudio; Kodsi, E.; Sircely, Jason A.; Haddad, F.; Hagen, C. von; Mapedza, Everisto D.; Wolderegay, K.; et al. (United Nations Convention to Combat Desertification, 2017)
With current rates of land degradation reaching ten to twelve million ha per year, there is an urgent need to scale up and out successful, profitable and resource-efficient sustainable land management practices to maintain the health and resilience of the land that humans depend on. As much as 500 million out of two billion ha of degraded land, mainly in developing countries, have restoration potential, offering an immediate target for restoration and rehabilitation initiatives.1 In the past, piecemeal approaches to achieving sustainable land management have had limited impact. To achieve the ambitious goals of alleviating poverty, securing food and water supplies, and protecting the natural resource base, we need to recognize the inter-connectedness of the factors driving land degradation, so that solutions can be taken to scale, transforming management practices for millions of land users. An analysis of the critical barriers and incentives to achieve scaling up suggests that the most appropriate options should be selected through the involvement of stakeholders at all levels, from local to national and international. New incentives for land managers as well as the public and private sectors are required to achieve a land degradation-neutral world.